Morphoea with Myositis: A Rare Association. (20th October 2011) - Sommerlad, Mary; Bull, Richard; Gorman, Claire
Abstract : In this case, we describe an unusual presentation of a young woman with a rash typical of morphoea (confirmed on biopsy), who went on to develop myositis in an atypical distribution. Although the association of myositis with diffuse systemic sclerosis is well described, the link with localised scleroderma (morphoea) and myositis has not been described.